KOMPETENSI MANAJERIAL KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU PADA MASA COVID-19 DI MTS 02 AL-MAARIF SINGOSARI - Rifqotul Hasanah; Abdul Jalil; Fita Mustafida (VICRATINA, 2021)
The presence of a virus that is often called Covid-19 causes limited activities. Activities that cause crowds are not allowed to be held. This has an impact, one of which is education. The level of performance and motivation of teachers at MTs Al-Maarif 02 Singosari is still very much needed. This is due to the inhibiting factors, with these factors affecting the managerial competence of the principal. Among these factors are internal and external. The internal factor is the lack of motivation from the teacher himself which causes his performance to decrease. Meanwhile, external factors such as support from the surrounding community and the lack of participation of parents in conducting online learning. Therefore, the efforts of school principals are needed to continuously improve teacher performance during the Covid-19 pandemic.